Aspek Hukum Korporasi dalam Perjanjian Keagenan dan Distributor - Suradiyanto Suradiyanto (Jurnal Aplikasi Manajemen, 2010)
Business transaction in a company or corporation could happened in a few form on each form having its own arrangement model. Arrangement of distributor and agent only one of the business transaction model. Company agent practically often compared to distributor frequently, though between both different from law terms facet. Company agent usually interpreted as a law terms where someone giving power to agent for and on behalf of principal full power do business transaction with third party (consumer). Principal full power will be in control of actions done by agent, as long as passed to authority boundary to it. While distributor action for and on behalf of alone. All law action related to business is distributor responsibility itself.